Effect of NR1D1 on the proliferation and differentiation of yak skeletal muscle satellite cells - Zhe, Yuqi; Wu, Zhijuan; Yasenjian, Sibinuer; Zhong, Jincheng; Jiang, Hui; Zhang, Ming; Chai, Zhixin; Xin, Jinwei (Frontiers in Veterinary Science, 2024)
The severe conditions at high altitudes, where yaks inhabit, contribute to delayed muscular growth and compromised tenderness of their muscle tissue. Myosatellite cells are responsible for the growth and regeneration of skeletal muscle after birth and have the potential to proliferate and differentiate, its development is closely related to meat quality, and the nuclear receptor gene NR1D1 is involved in muscle formation and skeletal muscle regulation. Therefore, in order to understand the effect of NR1D1 on muscle satellite cells, we identified the mRNA expression levels of marker genes specifically expressed in muscle satellite cells at different stages to determine the type of cells isolated. Eventually, we successfully constructed a primary cell line of yak muscle satellite cells. Then we constructed NR1D1 overexpression vector and interference RNA, and introduced them into isolated yak skeletal muscle satellite cells. We performed qPCR, CCK8, and fluorescence-specific to detect the expression of genes or abundance of proteins as markers of cell proliferation and differentiation. Compared with those in the control group, the expression levels of proliferation marker genes KI-67, CYCLIND1, and CYCLINA were significantly inhibited after NR1D1 overexpression, which was also supported by the CCK-8 test, whereas differentiation marker genes MYOD, MYOG, and MYF5 were significantly inhibited. Fluorescence-specific staining showed that KI-67 protein abundance and the number of microfilaments both decreased, while the opposite trend was observed after NR1D1 interference. In conclusion, we confirmed that NR1D1 inhibited the proliferation and differentiation of yak skeletal muscle satellite cells, which provides a theoretical basis for further research on the effect of NR1D1 on improving meat quality traits and meat production performance of yaks.